2019
DOI: 10.4103/ijcm.ijcm_44_19
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to healthy lifestyle among college-going students in a selected college in Bengaluru Urban district

Abstract: Context:Cardiovascular diseases (CVDs) are influenced by factors acting at all stages of life. Healthy lifestyle practices among adolescents and youth are crucial in preventing CVDs in the later years. Many barriers prevent young people from practicing healthy lifestyles.Aims:The aim of this study is to identify barriers to healthy lifestyle among college-going students in Bengaluru Urban District.Settings and Design:A cross-sectional study was conducted among 722 students aged 15–25 years, in a degree college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Similarly, a study conducted among Indian college students revealed that females faced more barriers to physical activity than males, resulting in low levels of physical activity. 23 Our study showed that large proportion of medical students exhibited poor dietary habits with low physical activity. Medical students who practiced these unhealthy eating habits were at risk of acquiring obesity and other metabolic diseases.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, a study conducted among Indian college students revealed that females faced more barriers to physical activity than males, resulting in low levels of physical activity. 23 Our study showed that large proportion of medical students exhibited poor dietary habits with low physical activity. Medical students who practiced these unhealthy eating habits were at risk of acquiring obesity and other metabolic diseases.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, a study conducted among Indian college students revealed that females faced more barriers to physical activity than males, resulting in low levels of physical activity. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, y según los hallazgos descritos surge la necesidad de desarrollar este tipo de investigaciones que ayuden a dilucidar y contrarrestar factores de riesgo en el largo plazo para el estudiante universitario, puesto que, uno de los perfilamientos que se encontró en el presente estudio revela que aquellos estudiantes que prefieren como estrategia de aprendizaje la lectoescritura, son al mismo tiempo estudiantes que manifiestan consumir drogas semanalmente y referir implicaciones personales en las actividades que desarrollan, hallazgos que han sido descritos en la literatura al mencionar que el consumo de drogas repercute considerablemente en el rendimiento académico (Wolaver, 2002;Arria et al, 2013) que pueden desencadenar morbilidad y mortalidad médica y psiquiátrica (Skidmore, Kaufman & Crowell, 2016;White et al, 2011). Los hallazgos de la presente investigación revelan que, dentro de los cinco perfilamientos de los estudiantes universitarios, aquellos estudiantes que no tienen hábitos saludables son al mismo tiempo quienes consumen eventualmente cigarrillo, drogas y alcohol, y, al mismo tiempo tienen dificultades para resolver las situaciones cotidianas que le presente su contexto, conclusiones que han sido documentadas en otros estudios al referir que las futuras enfermedades cardiovasculares que se desencadenan por una disminución de la CF y los estilos de vida en la vida universitaria deben ser estudiadas en respuesta a cada contexto (Morales et al, 2013;Fernandes et al, 2013;Kutlu & Erden, 2013;Chitra et al, 2019).…”
Section: Discussionunclassified
“…Por otra parte, es importante resaltar la relevancia que tiene el hecho de llevar estilos de vida saludables, dado que, se asocian con un mejor control cognitivo y rendimiento académico (Dubuc et al, 2019). Y, por el contrario, son diversas las enfermedades cardiovasculares que pueden desencadenar inadecuados estilos de vida en la transición de adolescentes y jóvenes (Chitra et al, 2019). La OMS define a los jóvenes, cómo aquellos que se encuentran en las edades comprendidas de los 15 a los 24 años Al mismo tiempo, se ha encontrado que los estudiantes deben desarrollar adaptaciones de orden cognitivo y físico para contrarrestar enfermedades futuras (Zhou et al, 2012), siendo la competencia de AaA un elemento crucial que debe relacionarse con el contexto personal del estudiante (Becerra-Patiño & Escorcia-Clavijo, 2023), dado que, si no se desarrollan estilos de vida enmarcados en la salud y la cognición, puede constituir en factores de riesgo que prevalecen a lo largo de la vida (Nagheer et al, 2017).…”
Section: Introductionunclassified
“…The over-all mean reveal that health-promoting behaviors are met sometimes (x̄ = 2.63) among college students, indicating that their health profile is frequently, albeit not consistently, attended to. It is common among adolescents to encounter impediments when it comes to sustaining a healthy lifestyle, as Tomy et al (2019) have noted. Stress has been identified as the most significant barrier, followed by diet, for college students.…”
Section: Levels Of Health-promoting Lifestyle Of College Studentsmentioning
confidence: 99%